Mexicanolide limonoids with in vitro neuroprotective activities from seeds of Khaya senegalensis1. Issue 51 (5th June 2015) - Li, Hui; Li, Yi; Wang, Xiao-Bing; Pang, Tao; Zhang, Lu-Yong; Luo, Jun; Kong, Ling-Yi
<x xml:space="preserve">Abstract</x> Fourteen new mexicanolide-type limonoids khasenegasins A–N (1–14) were isolated from the seeds of Khaya senegalensis, and bioactivity scan indicated that these mexicanolide-type limonoids displayed neuroprotective activities.